Effect of Preschool Home Visiting on School Readiness and Need for Services in Elementary School: A Randomized Clinical Trial - Bierman, Karen L. (JAMA Pediatr, 2018)
IMPORTANCE: Home visiting programs targeting the school readiness of preschool children (age range, 4-5 years) show promise in short-term and quasi-experimental studies but rarely are evaluated with rigorous designs and follow-up assessments. OBJECTIVES: To examine the sustained effects of a preschool home visiting program on child and family competencies and on child need for services 4 years later. DESIGN, SETTING, AND PARTICIPANTS: In a randomized clinical trial, individual families with preschool children were assigned to receive the Research-Based and Developmentally Informed–Parent home visiting program (REDI-P) (intervention group) or math home learning games in the mail (control group). Follow-up assessments occurred in third grade. Families were recruited from 24 Head Start centers in 3 Pennsylvania counties serving rural and urban areas. Four-year-old children from 200 low-income families participated. Families were recruited in fall 2008 and fall 2009. The follow-up data used were collected in spring 2013 and spring 2014. The analyses were conducted in 2016 to 2017. INTERVENTIONS: REDI-P visits followed a well-specified curriculum, with 10 home visits during preschool and 6 booster visits in kindergarten. Parents received coaching to enhance parent-child relationships and home learning materials to support child development and school readiness. MAIN OUTCOMES AND MEASURES: Intervention focused on boosting competencies in academic performance and social-emotional adjustment and reducing child problems at home. Direct assessments, teacher ratings, and parent reports were collected. In addition, third-grade teachers recorded all services that children needed and received at school. RESULTS: Two hundred participating children (110 [55.0%] white, 52 [26.0%] black, and 38 [19.0%] Latino; 112 [56.0%] male) had a mean (SD) age of 4.45 (0.29) years at the start of intervention. Third-grade outcomes were available for 153 (76.5%) of the initial sample and revealed statistically significant effects on multiple measures in each competency domain. In addition, REDI-P reduced child need for educational and mental health services at school. Significant effect sizes were small to moderate, averaging approximately one-third of 1 SD (Cohen d = 0.27 to 0.45). Mediation models demonstrated that intervention effects on services were accounted for by intervention effects on the targeted competencies. CONCLUSIONS AND RELEVANCE: REDI-P produced sustained benefits evident 4 years after intervention, significantly reducing child need for school services. The results of this study appear to validate the value of preschool home visiting as a strategy to help close the gap in school readiness and child well-being associated with poverty.